OTOLARYNGOLOGICAL MANIFESTATIONS OF COVID-19 IN MADINAH DISTRICT PATIENTS, BASRAH, IRAQ - Haider Kadhem Saeed; Ziyad Tariq Malghooth; Rafad Abdulazeez Adduljaleel (Web of Journals Publishing, 2023)
Objective: To find out the presence of otorhinolaryngological symptoms in PCR confirmed Covid-19 patients in Almadinah district, Basra, Iraq.